The Borrowing Behaviour of Households: Evidence from the Cyprus Family Expenditure Surveys - Andreou, Sofia N. (My University, 2011)
This study investigates how various factors affect households demand for borrowing in Cyprus using data from the Family Expenditure Surveys for the years 2002/03 and 2008/09. The descriptive statistics show that middle income households with a younger age head have relatively high gross debt-to-income ratios; whereas upper income households with an older age head tend to have relatively high gross deposits-to-income ratios. The econometric analysis uses smooth (over the life cycle) income to investigate the extent to which household borrowing at a given point in time conforms to long term expectations about future income. The results conform to theoretical expectation insofar as demand for loans is determined by smooth, not current, income. This can be interpreted as an indication that the borrowing behavior of households in Cyprus is rational. Nevertheless, the results in the paper need to be confirmed by further analysis to also account for the dynamics of the borrowing-saving behavior of households. This will be possible when the Household Finance and Consumption Survey is available in Cyprus, hopefully in the near future.
Keywords: Household debt; Household savings; Smooth income; Cyprus family expenditure surveys